Geochemical-isotopic characteristics and K-Ar ages of magmatic rocks from Hundar valley, Shyok Suture Zone, Ladakh - Ahmad, T; Sivaprabha, S; Balakrishnan, S; Thanh, NX; Itaya, T; Sachan, HK; Mukhopadhyay, DK; Khanna, PP (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1229 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.18